On being a theologian for “others” - Ackerman, Denise M (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
This contribution, written in the form of a letter to Dirkie Smit, reflects on his weekly columns that are published in the Cape newspaper Die Burger. It addresses two questions: How does Smit, par essence a theologian’s theologian, communicate so successfully with the readers of a newspaper? Second, what motivates his faithful writing of these weekly columns? In attempting to address the first question it is suggested that the columns are infused with the intent to achieve a communicative praxis that is liberating, and thus reminiscent of critical theory. Employing language that is simple and straightforward, laced with humour, never devoid of learning, and contextually relevant, Smit’s columns are a highly effective exercise in Christian ethics. Here the two questions asked, merge, for the answer to the question of motivation is found to be an expression of Smit’s spirituality and his hope for a redeemed world. Discernment (onderskeidingsvermoë), a key value in Christian spirituality, is central to his writing. His critical contextual awareness combined with his focus on moral discernment, all couched in a highly accessible format, make him “a theologian for others”.